Entrepreneurial career choice and characteristics of engineering and business students. - Johnson, Sara K. (Tufts University. Tisch Library., 2016)
This paper measures the entrepreneurial intent and related characteristics of engineering undergraduates, as comparedwith business students. The purpose of this study is to describe and test the difference on entrepreneurial intent and relatedcharacteristics for engineering and business students with different career goals for both genders.